2015
DOI: 10.3390/molecules201018597
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of the Major Constituents in Shexiang Tongxin Dropping Pill by HPLC-Q-TOF-MS/MS and UPLC-QqQ-MS/MS

Abstract: Shexiang Tongxin dropping pill (STP) is a traditional Chinese medicine formula that consists of total saponins of ginseng, synthetic Calculus bovis, bear gall, Venenum bufonis, borneol and Salvia miltiorrhiza. STP has been widely used in China and Southeast Asia for the treatment of cardiovascular diseases. In this study, a qualitative analytical method using high performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry was developed for identification of the major cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…STDP is a formulate traditional Chinese Medicine widely used to treating clinical cardiovascular disease, especially in stable angina pectoris in China and South Asia. [ 13 – 16 ] It is a complex herb formula, ultra performance liquid chromatography coupled with triple-quadrupole tandem mass spectrometry (UPLC QqQ-MS/MS) Quantitative Analysis revealed 13 major chemical constituents in STDP, [ 17 ] which has the functions of dilating blood vessels, anti-inflammatory and reducing endothelial damage. Previous studies have revealed that STDP has a significant improvement on myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…STDP is a formulate traditional Chinese Medicine widely used to treating clinical cardiovascular disease, especially in stable angina pectoris in China and South Asia. [ 13 – 16 ] It is a complex herb formula, ultra performance liquid chromatography coupled with triple-quadrupole tandem mass spectrometry (UPLC QqQ-MS/MS) Quantitative Analysis revealed 13 major chemical constituents in STDP, [ 17 ] which has the functions of dilating blood vessels, anti-inflammatory and reducing endothelial damage. Previous studies have revealed that STDP has a significant improvement on myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the values of LOD and LOQ under our method were less than the compounds in other references. [ 5 6 ]…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a total of 105 compounds were identified or tentatively characterized from YXS Tablet. These compounds include 25 phenanthraquinones, 11 lactones, 19 lignans, 24 acids, and 26 other compounds [13][14][15][16][17][18][19][20][21][22]. Their retention times, molecular formulas, high-resolution MS data, and high-resolution MS 2 fragment ions are summarized in Table 1.…”
Section: Qualitative Determination Of Yxs Tabletmentioning
confidence: 99%